2021
DOI: 10.3389/fcell.2020.621070
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Functions of CAFs Secretome During Cancer Progression and Therapy

Abstract: Multiple lines of evidence are indicating that cancer development and malignant progression are not exclusively epithelial cancer cell-autonomous processes but may also depend on crosstalk with the surrounding tumor microenvironment (TME). Cancer-associated fibroblasts (CAFs) are abundantly represented in the TME and are continuously interacting with cancer cells. CAFs are regulating key mechanisms during progression to metastasis and response to treatment by enhancing cancer cells survival and aggressiveness.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 235 publications
(248 reference statements)
1
61
0
Order By: Relevance
“…One example is the multifunctional cytokine TGF-β that, in physiological conditions, regulates different mechanisms, such as morphogenesis, development, wound healing, and others, while, if deregulated, can promote aggressive phenotypes in cancers. Once activated, CAFs can secrete various messengers that can promote invasion and metastasis [ 69 ]. Some of these factors enhance EMT or ECM remodeling, as discussed in previous paragraphs.…”
Section: Caf–tumor Communicationmentioning
confidence: 99%
“…One example is the multifunctional cytokine TGF-β that, in physiological conditions, regulates different mechanisms, such as morphogenesis, development, wound healing, and others, while, if deregulated, can promote aggressive phenotypes in cancers. Once activated, CAFs can secrete various messengers that can promote invasion and metastasis [ 69 ]. Some of these factors enhance EMT or ECM remodeling, as discussed in previous paragraphs.…”
Section: Caf–tumor Communicationmentioning
confidence: 99%
“…On the other hand, radiotherapy was proposed to increase paracrine signaling between fibroblasts and tumor cells via insulin-like growth factor (IGF) and TGF-b pathways (291,292). Chemotherapy can also modulate the tumor microenvironment (293). CAF derived growth arrest-specific protein 6, which is a ligand of TAM receptors, was reported to increase during cisplatin based chemotherapy (294).…”
Section: Recruitment and Polarization Of Tams By Cafsmentioning
confidence: 99%
“…In fact, the induction of the cyclooxygenase-2 (COX-2)/prostaglandin E2 cascade induced by HP infection leads to the hypermethylation of miR-149 in CAFs, eventually resulting in increased IL-6 secretion [94]. Based on these premises and given the role played by IL-6 in inducing EMT through the JAK2/STAT3 pathway, recent studies have investigated the role of neutralizing antibodies, including AG490 [95,96]. A study conducted by Wu and colleagues has suggested that the simultaneous inhibition of JAK2/STAT3 and IL-6 using AG490 might impair tumor diffusion induced by CAFs to the peritoneum; as such, IL-6-targeted therapies could represent a complementary treatment approach due to their action on fibroblasts [97].…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%